Participation, Democratic Deficit and Good Regulation: a Case Study of Participatory Strategies in the European Regulation of GMO Products - Ferretti, Maria Paola (2006)
Abstract: In the European Union, the institutional reform that risk regulation system has undergone in the last decade has emphasised the need for fostering public participation and stakeholder involvement in decision making processes. Citizen scrutiny, in theory, ought to bring about better governance, and greater participation in public policy decisions is usually regarded as a symptom of a healthy democracy. By presenting evidence from two case studies in the field of bio-technology regulation, this paper aims to prove that taking participation as a tout court advantage is a mistake